The Saga of Pennsylvania’s “Willie Horton” and the Commutation of Life Sentences in the Commonwealth - Austin, Regina (2020)
In 1994, Reginald McFadden’s sentence of life without the possibility of parole was commuted by the governor of Pennsylvania, and he was shipped to New York to be supervised by a bunch of amateurs. Within roughly 90 days, he murdered two people, raped and kidnapped a third, and possibly murdered a fourth. McFadden proved to be Lieutenant Governor Mark Singel’s “Willie Horton.” Singel, who had voted for McFadden’s release as a member of the Board of Pardons, lost the gubernatorial election to his Republican opponent who ran on a “life-means-life” platform. Compounding the tragedy of McFadden’s actions, the Pennsylvania Constitution was amended to require a unanimous vote of the pardon board for the commutation of life sentences. In the last 25 years, only 25 lifers have won commutation, 19 of whom were freed by the current chief executive, Governor Wolf. Drawing on materials culled from the state archives and right-to-know requests, this article, which has the makings of a serial podcast, explores the bureaucratic blunders and biased judgments that have left a large number of aging rehabilitated lifers to await death by incarceration. The Article ends with proposals for reform the commutation process to counter the fear of the “Willie Horton Effect” experienced by public officials involved in pardon decisions